Research on the Development and Comparison of Cuisine in China, India, and Japan - Au EnTong (SHS Web of Conferences)
There are both similarities and differences in the cuisine cultures of China, India, and Japan. The cuisine of the Three Kingdoms was initially influenced by ancient China. However, as they developed their own unique cuisine cultures, they were influenced by various factors such as religion, geography, and history, carrying rich national culture and spirit. The similarities and differences in the cuisine of the Three Kingdoms, while rooted in daily dietary practices, hold significant research value. This paper will analyze and explore the characteristic similarities and differences among Chinese, Japanese, and Indian cuisines, and examine their shared traits and cultural significance.